REACTIVITY OF RECENTLY DEPOSITED ORGANIC MATTER: DEGRADATION OF LIPID COMPOUNDS NEAR THE SEDIMENT-WATER INTERFACE - Canuel E.A.; Martens C.S. (My University, 1996)
The usefulness of biomarker compounds buried in marine sediments depends upon a quantitative understanding of the effects of early diagenesis on their distribution. To address this, a new experimental approach was utilized to determine rates of degradation in a coastal sediment. Rates of degradation for solvent-extractable lipid components were quantified in four sediment horizons composed of newly accumulated organic matter (31-144 days since deposition). Sediment accumulation rate data derived from changes in the inventory of Be-7 (t1 = 53.3 days) were combined with concentration data for lipid biomarker compounds, enabling us to evaluate the reactivity of organic matter in the upper 8 cm of the rapidly accumulating sediments of Cape Lookout Bight, North Carolina, USA (CLB). Net rates of loss and rate constants were calculated for individual compounds belonging to three classes of lipids: fatty acids, sterols, and n-alkanes. Individual components showed a range in reactivity, in some cases (fatty acids), attributable to differences in their biological sources. Rates and rate constants were consistently highest in the surficial sediments (0-2.5 cm), indicating that the reactivity of a given molecule(s) decreases over time, and beginning soon after deposition. Comparison with apparent rate constants (k') calculated over longer timescales (one and ten years) shows that steady-state diagenetic models underestimate rates of degradation at or near the sediment-water interface by an order of magnitude.